Pemetaan Tingkat Kerentanan Daerah terhadap Penyakit Menular (TB Paru, DBD, dan Diare) di Kabupaten Lumajang Tahun 2012 (Mapping of District Vulnerability on Communicable Diseases (Pulmonary TB, DHF, and Diarrhea) in Lumajang 2012) - Laras Fitria; Pudjo Wahjudi; Dwi Martiana Wati (UPT Percetakan dan Penerbitan Universitas Jember, 2014)
Several types of communicable diseases such as pulmonary TB, DHF, and diarrhea have some similarity of physical environmental, socio economic, and host factors. Data related communicable diseases are needed to produce health information. Processing and presentation data about health in Lumajang is still very simple, that's only based on amount of cases distribution without any assessment with other factors such as physical environmental and human activity that have contributed to a health-related phenomena. The purposes of this research are to create synthesis thematic maps in the form of district vulnerability of communicable diseases with combining environmental and host factors. This type of research is descriptive study with variables are physical environmental (height and rainfall), social economic environment (category of family, population density rate, and total of family member), host (age, sex, and behavior), and prevalence rate of communicable diseases where obtained from secondary data. The data prensented in the form of vulnerability maps using crosstab. The result of synthesis thematic maps that subdistricts with vulnerable category of pulmonary TB are Klakah, Gucialit, Kedungjajang, Sukodono, Jatiroto, Lumajang, Yosowilangun, Kunir, Pasirian, Tempursari, Pronojiwo, Candipuro, and Pasrujambe. The subdistricts with vulnerable category of DHF are Senduro, Sukodono, Kunir, dan Rowokangkung. The subdistricts with vulnerable category of diarrhea are Senduro, Sukodono, Kunir, dan Rowokangkung. The most of subdistricts are invulnerable on communicable diseases. Keywords: Mapping, vulnerability, communicable diseases.